The Effect of NPWP Ownership Obligations, Tax Audits and Tax Collection on Tax Revenue - Raden Ai Lutfi; Rananda Septanta; Chaeru Syahru Ramdhani; Adi Sofyana Latif (Syntax Corporation Indonesia, 2023)
Stand up comedy Indonesia is a talent search event held by Kompas TV. This type of verbal humor is more dominant than nonverbal. The language used in humor is different from the language used in serious communication. This study aims to analyze the humorous discourse in stand up comedy